Workshop report: GHG emissions mitigation for dairy systems in Kenya - Gonzalez Quintero, Ricardo; Isiaho, Glarion; Kipkosgei, Solomon; Sisay, Henock; Sibiko, Kenneth Waluse (2024)
This report details the proceedings of the workshop focused on promoting greenhouse gas (GHG) emissions mitigation strategies in Kenya’s dairy production systems. The workshop aimed to engage stakeholders, including dairy farmers, agricultural experts, and project staff, in discussions on feasible approaches to reducing GHG emissions while maintaining or enhancing productivity in dairy farming. Two workshops were conducted: the first, on July 24, 2024, specifically for women dairy farmers, and the second, on July 25, 2024, for men farmers. Each workshop was divided into two segments: a field visit to demonstration farms and a conference room session. During these sessions, participants were engaged in presentations, discussions, and exercises addressing the social and technical aspects of adopting GHG mitigation interventions. The key outcomes of the workshops included an enhanced understanding of GHG mitigation measures, validation of intervention strategies, and feedback on the challenges and benefits of implementing these strategies within Kenyan dairy farming systems.